1981
DOI: 10.1113/jphysiol.1981.sp013999
|View full text |Cite
|
Sign up to set email alerts
|

Effects of endogenous and exogenous noradrenaline on the smooth muscle of guinea‐pig mesenteric vein

Abstract: SUMMARYMembrane responses of smooth muscles of the guinea-pig mesenteric vein to noradrenaline released from perivascular nerves or applied exogenously were investigated.1. Exogenously applied noradrenaline depolarized the muscle membrane at concentrations ofover 10-6 M, and generated slow waves or action potentials. Application of phentolamine but not propranolol suppressed the depolarization.2. The depolarization induced by exogenous noradrenaline was associated with increase in the membrane resistance. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
101
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(111 citation statements)
references
References 32 publications
(41 reference statements)
10
101
0
Order By: Relevance
“…Recent results obtained from single venous smooth muscle cells indicated that the NA-induced depolarization is mainly mediated by an increase in chloride conductance (Byrne & Large, 1988a;Van Helden, 1988;Pacaud et al, 1989). However, an increase in a non-specific cation channel (Byrne & Large, 1988b) and a decrease in potassium conductance (Suzuki, 1981) could also be involved.…”
Section: Introductionmentioning
confidence: 99%
“…Recent results obtained from single venous smooth muscle cells indicated that the NA-induced depolarization is mainly mediated by an increase in chloride conductance (Byrne & Large, 1988a;Van Helden, 1988;Pacaud et al, 1989). However, an increase in a non-specific cation channel (Byrne & Large, 1988b) and a decrease in potassium conductance (Suzuki, 1981) could also be involved.…”
Section: Introductionmentioning
confidence: 99%
“…Two other ionic mechanisms 1 Author for correspondence. involved in noradrenaline action have been described: an increase in a non specific cation channel (Byrne & Large, 1988b) and a decrease in potassium conductance (Suzuki, 1981; Van Helden, 1988). Furthermore, noradrenaline increases the cytoplasmic calcium concentration as measured with fluorescent indicators (Satoh et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the guinea-pig mesenteric artery, sympathetic nerve stimulation gives rise to rapidly rising excitatory junction potentials of brief duration that are resistant to prazosin, but are blocked by α,β-meATP [67,82]. In contrast, in the guinea-pig mesenteric vein a slow depolarization [166] that is resistant to purinoceptor desensitization with α,β-meATP [65,67] is observed rather than fast EJPs. This has led to the conclusion that ATP is not involved in these junctional events [65,67] and, hence, is not released during nerve stimulation.…”
Section: Effects Mediated By P2x and P2y Receptors In The Splanchnic mentioning
confidence: 99%